The Impact of the Morning Literacy Program and Literacy Breakfast Program on Students' Academic Achievement in SD Negeri 1 Menganti, Sruweng - Shaharani, Aisha Qonita; Pratama, Faizal Jefri; Dhiyaa, Ananda Rining; Islami, Syahara Nur; Beryl, Sharla Aurellia; Falah, Sultan Rafi; Hambara, Radheya; Setiawan, Muhamad Aldi; Jannah, Indah Nur; Fadhila, Syifa Aisyah; Arkhamah, Desta Putri; Sulaeman, Sulaeman; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Students are the future generation of the nation who need to be equipped with positive habits to support their academic achievement. Two important activities that can be implemented in the morning are morning literacy and literacy breakfast. Morning literacy is the activity of reading books before classes begin, and literacy breakfast is the activity of doing light questions before learning begins. Morning literacy aims to build reading interest and comprehension skills, while literacy breakfast aims to train concentration, critical thinking, and mental readiness in students to face lessons. The method used in implementing this program is a quantitative method, with data collection conducted through pre-test and post-test. The research subject consisted of 38 fourth-grade and fifth-grade students at Menganti Elementary School. The results of the program implementation showed an increase in students' learning motivation, concentration, and academic performance. In order to maximize the results of literacy programs at the elementary school level, the implications of this study highlight the importance of strengthening existing literacy strategies, providing adequate support facilities, and educating teachers.